1997
DOI: 10.1097/00003246-199701000-00033
|View full text |Cite
|
Sign up to set email alerts
|

A delivery system for inhalation of nitric oxide evaluated with chemiluminescence, electrochemical fuel cells, and capnography

Abstract: An accurate precision in delivered nitric oxide concentration was achieved during intermittent flow ventilation, and this accuracy was independent of tested ventilator settings. The delivery system administered an almost stable concentration throughout a respiratory cycle and during long-term delivery. If the mixing point is in the inspiratory part of the ventilator, valid measurement of nitric oxide and nitrogen dioxide delivery concentrations are possible. Both techniques for measuring nitric oxide and nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Moutafis et al reported on Table 1. Percentage difference between set concentrations of [NOi] target and measured concentrations of NOi in the present work and a study by Lindberg et al[3]. Values are presented as mean ± SEM…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Moutafis et al reported on Table 1. Percentage difference between set concentrations of [NOi] target and measured concentrations of NOi in the present work and a study by Lindberg et al[3]. Values are presented as mean ± SEM…”
supporting
confidence: 49%
“…To answer this question, a comparison with studies on validation of chemoelectric cells may be helpful, since a dosage of NOi based on chemoelectric cells is accepted as safe and reproducible. Only a few studies addressing this issue, however, give sufficient data for a comparison with our work: Lindberg et al gave data from readings of their electrochemical cells when [NOi] was set at 10, 60, and 100 ppm [3]. For comparison, their results of "percentage differences" (calculated as ( the validation of a chemoelectric monitor against a chemiluminescence monitor [5].…”
Section: Accuracy Of Dosagementioning
confidence: 96%
“…This regulatory system maintains the concentration of nitric oxide almost constant during inspiration and expiration, despite changes in minute ventilation, oxygen concentration, mode of ventilation (pressureregulated, volume-regulated), inspiratory time, pause time, frequency, etc. 9 A paediatric silicon tube, 0.85 m in length, attached to the ventilator and a canister (diameter 0.07 m, height 0.075 m, volume 290 ml) containing the nitrogen dioxide absorbing material, was connected to the tube by an adapter. The same canister was used for all three materials to minimize differences in volume-dependent absorption and to standardize the deadspace volume on each side of the canister during the tests.…”
Section: Methodsmentioning
confidence: 99%
“…In the Servo Ventilator 300, nitric oxide is injected into the inspiratory limb and the injection is adjusted very rapidly (ms) as the main ventilatory gas flow (air and oxygen) varies during the respiratory cycle. This method of mixing maintains a constant concentration of nitric oxide in the inspired gas at different ventilatory settings (16), which may be important since peak concentrations of nitric oxide have been shown to give high concentrations of nitrogen dioxide (15,17). The concentration of nitrogen dioxide is also dependent on the point at which the nitric oxide/nitrogen stock gas solution is mixed into the ventilatory system, since this may affect the residence time of ni-tric oxide with oxygen.…”
Section: Fig 3 Concentrations Of Nitric Oxide and Nitrogen Dioxide mentioning
confidence: 99%